Cereal policies review 1997 - 1998 - FAO (FAO, 1999)
This review consists of a survey of developments in national cereal policies during the past year. The materials are organized under various sections, each examining the main target variable of policy intruments: production; consumption; marketing and stocking; and trade. The information was collected from a variety of sources, including FAO policy questionnaries, new agencies, government and FAO reports.